ChemInform Abstract: Flow Chemistry on Multigram Scale: Continuous Synthesis of Boronic Acids within 1 s. Issue 51 (5th December 2016) - Hafner, Andreas; Meisenbach, Mark; Sedelmeier, Joerg
Abstract: A continuous flow setup for organolithium chemistry on a multigram scale is described.